Strain-specific effect of Streptococcus thermophilus consumption on host physiology - Peng Yu; Yang Jiang; Yuqi Pan; Min Guo; Bo Yang; Xiaoming Liu; Jianxin Zhao; Hao Zhang; Wei Chen (Food Science and Human Wellness)
Streptococcus thermophilus is one of the most prevalent species in stool samples of westernized populations due to continuous exposure to fermented dairy products. However, few studies have explored the effect on host physiology by multiple S. thermophilus strains and considered the inter-strain differences in regulating host. In the present study, we investigated how four S. thermophilus strains influenced the gut microbiota, mucin changes, and host metabolism after 28 days of intervention in conventional mice. The results indicated that the consumption of S. thermophilus affected the host with strain specificity. Among four S. thermophilus strains, DYNDL13-4 and DQHXNQ38M61, especially DQHXNQ38M61, had more effect on host physiology by modulating gut microbiota and host metabolism than LMD9 and 4M6. Ingestion of strains DYNDL13-4 and DQHXNQ38M61 resulted in more remarkable changes in amino acid metabolism and lipid metabolism than that of strains LMD9 and 4M6, which may be related to the elevation of intestinal Bifi dobacterium by DYNDL13-4 and DQHXNQ38M61. The enriched Coriobacteriaceae UCG-002, Rikenellaceae RC9 gut group, and Lactobacillus only in the DQHXNQ38M61 group, had a close relationship with the prominent effect of DQHXNQ38M61 on regulating amino acid and lipid metabolism. In addition, DQHXNQ38M61 had a strong influence on degrading colonic mucin fucose by decreased α-fucosidase activity in feces, and improving mucin sulfation by upregulated Gal3ST2 expression. Comparative genomic analysis revealed that the four S. thermophilus strains belonged to different branches in the phylogenetic tree, and DYNDL13-4 and DQHXNQ38M61 had more genes involved in carbohydrate metabolism, amino acid metabolism, membrane transport, and signal transduction, which may confer the capacity of nutrient utilization and gastrointestinal adaptation of the strains and be associated with their strong regulation in host. Our study provides valuable information for understanding the regulation of host metabolism after consuming different S. thermophilus strains and could facilitate potential personalized applications of S. thermophilus based on strain varieties.